Cnidium officinale extract and butylidenephthalide inhibits retinal neovascularization in vitro and in vivo. Issue 1 (December 2016) - Lee, Yun; Lee, Yu-Ri; Kim, Chan-Sik; Jo, Kyuhyung; Sohn, Eunjin; Kim, Jin; Kim, Junghyun
Abstract Background Retinal neovascularization, which is the pathological growth of new blood vessels, is associated with retinopathy of prematurity, neovascular age-related macular degeneration, diabetic retinopathy and retinal vein occlusion. In this study, we evaluated the effect of an extract ofCnidium officinale Makino (COE) and its bioactive compound, butylidenephthalide (BP), on the migration and tube formation of human umbilical vein endothelial cells (HUVECs), and on retinal pathogenic neovascularization in the oxygen-induced retinopathy (OIR) mouse model. Method The HUVECs were incubated with COE and BP (0.1–10 μg/ml). The mice were exposed to 75 % oxygen for 5 days starting on the 7th postnatal day (P7–P12). Then, the mice were returned to room air and intraperitoneally injected with COE (100 mg/kg) and BP (5 mg/kg) once per day for 5 days (P12–P16). On P17, we measured retinal neovascularization and analyzed the angiogenesis-related proteins expression using protein arrays. Results COE and BP inhibit the HUVECs migration and the tube formation in a dose-dependent manner. In addition, COE significantly decreased retinal neovascularization in the OIR mice. COE reduced the expression levels of AREG, ANG, DLL4, Endostatin, IGFBP-2 and VEGF. Additionally, BP also inhibited the retinal neovascularization and down-regulated the expression of AREG, ANG, DLL4 and VEGF. Conclusion These results suggest that COE and BP exerts antiangiogenic effects on retinal neovascularization by inhibiting the expression of AREG, ANG, DLL4 and VEGF, indicating that antiangiogenic activities of COE may be in part due to its bioactive compound, BP.